2020
DOI: 10.3389/fphys.2020.00427
|View full text |Cite
|
Sign up to set email alerts
|

Posttranslational Arginylation Enzyme Arginyltransferase1 Shows Genetic Interactions With Specific Cellular Pathways in vivo

Abstract: Arginyltransferase1 (ATE1) is a conserved enzyme in eukaryotes mediating posttranslational arginylation, the addition of an extra arginine to an existing protein. In mammals, the dysregulations of the ATE1 gene (ate1) is shown to be involved in cardiovascular abnormalities, cancer, and aging-related diseases. Although biochemical evidence suggested that arginylation may be involved in stress response and/or protein degradation, the physiological role of ATE1 in vivo has never been systematically determined. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Recently, we began exploring the genetic interactions between ATE1 and thousands of other genes in the fission yeast model system ( Schizosaccharomyces pombe ) (Wiley et al, 2020 ). In this study, we observed that ATE1 interacts with only 5% of other yeast genes in a screening library covering 75% of the predicted open reading frames (ORF).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we began exploring the genetic interactions between ATE1 and thousands of other genes in the fission yeast model system ( Schizosaccharomyces pombe ) (Wiley et al, 2020 ). In this study, we observed that ATE1 interacts with only 5% of other yeast genes in a screening library covering 75% of the predicted open reading frames (ORF).…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondria are the main source of oxidative stressors in cells, and studies have shown that the expression of ATE1 increases in proportion to the degree of various stresses [ 39 ]. A large number of genes (at least 19) related to mitochondria or energy production, such as Oma1 and COQ7, were found to have genetic interactions with ATE1 through GO term studies, and those partial proteins have been reported to be involved in the regulation of cardiac hypertrophy [ 56 – 58 ]. Future studies would be required to study which proteins/factors are involved in LIQ downregulating ATE1 expression and its relationship with anticardiac hypertrophy from the stress response.…”
Section: Discussionmentioning
confidence: 99%
“…This reduction was presumably due, in part, to cycle progression (Stendel et al, 2007). A subset of genes in the Rho GTPase family (Rho A, B, C) were shown to interact with Ate1, using a systematic approach (Willey et al, 2020). These studies suggest that Ate1 is associated with cytoskeletal signaling pathways during OL development, and that changes in their regulators can lead to pathological states.…”
Section: Specific Ate1 Deletion In Ols Reduces Number Of Actin Filaments During Myelination In Vivomentioning
confidence: 94%